The evaluation of various kinetic models for base-catalyzed ethanolysis of palm oil - Shahla, S.; Ngoh, G.C.; Yusoff, R. (Bioresource Technology, 2012)
In this paper, the kinetics of palm oil ethanolysis with various models have been investigated in a temperature range of 25-55 degrees C. The highest yield was achieved when the conversion to ethyl ester was 97.5+/-0.5 in the stated temperature range, using ethanol:oil molar ratio of 12:1, and 1.0 wt. sodium ethoxide. The level of conformity of the reaction with reversible second order, irreversible second order and first order kinetic models were evaluated by means of the R-2 values of the linear curves. The ethanolysis showed the best conformity with irreversible second order kinetic model with 92-98 level of confidence. The reaction rate constants were within 0.018-0.088 dm(3)/mol min and the activation energy of the reaction was 42.36 kJ/mol.